The Jesus handbook - Schröter, Jens 1961-; Jacobi, Christine 1979-; Brawley, Robert L. 1939- (Grand Rapids, Michigan William. B. Eerdmans Publishing Company, 2022)
"An international collection of scholarship on Jesus of Nazareth, his world, the outcomes of his life, and the quest to locate him in historical context"--
"An authoritative collection of first-rate scholarship on Jesus, his world, the outcomes of his life, and the quest to locate him in history. The Jesus Handbook is an indispensable reference work featuring essays from a team of renowned international scholars on the significance and meaning of the life of Jesus of Nazareth. Rooted in historical-critical methodology, it emphasizes a diversity of perspectives and provides a spectrum of possible interpretations rather than a single unified portrait of Jesus. The Handbook's dozens of authors-Jewish, Roman Catholic, and Protestant-each remain committed to the principle of interpreting the life of Jesus in context, while also giving due diligence to the implications of archaeological evidence and recent discourses in the hermeneutics of history. After an introduction that lays out the considerations of the task at hand, the authors survey the history of Jesus research and take a close look at the historical material itself-textual and otherwise. From this foundation, the Handbook then details the life of Jesus before at last exploring the reception and effects of Jesus's life after his death, especially in the first centuries CE. With this wealth of information available in a single volume, scholars and students of the New Testament and early Christianity-and anyone interested in the search for the historical Jesus-will find The Jesus Handbook to be a resource that they return to time and again for both its breadth and depth.Contributors:Sven-Olav Back, Knut Backhaus, Reinhard von Bendemann, Albrecht Beutel, Darrell L. Bock, Martina Böhm, Cilliers Breytenbach, James G. Crossley, Lutz Doering, Martin Ebner, Craig Evans, Jörg Frey, Yair Furstenberg, Christine Gerber, Katharina Heyden, Friedrich Wilhelm Horn, Stephen Hultgren, Christine Jacobi, Jeremiah J. Johnston, Thomas Kazen, Chris Keith, John S. Kloppenborg, Bernd Kollmann, Michael Labahn, Hermut Löhr, Tobias Nicklas, Markus Öhler, Martin Ohst, Karl-Heinrich Ostmeyer, James Carleton Paget, Rachel Schär, Eckart David Schmidt, Daniel R. Schwartz, Markus Tiwald, David du Toit, Joseph Verheyden, Samuel Vollenweider, Ulrich Volp, Annette Weissenrieder, Michael Wolter, Jürgen K. Zangenberg, Christiane Zimmermann, and Ruben Zimmermann"--
"Originally published in German by Mohr Siebeck GmbH & Co. KG Tübingen under the title Jesus Handbuch, 2017 Mohr Siebeck Tübingen."
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Teachings; Jesus Christ -- Person and offices; Jesus Christ -- History of doctrines; RELIGION / Biblical Studies / New Testament / Jesus, the Gospels & Acts; RELIGION / Biblical Reference / Dictionaries & Encyclopedias